The shadow prince - Durham, David Anthony, 1969- (Tu Books, an imprint of Lee & Low Book, Inc., 2021)
"In this middle grade solarpunk novel set in an alternate Egyptian universe, twelve-year-old Ash must compete and survive to become the shadow-and protector-of the prince"--